2009
DOI: 10.1002/dc.21013
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of lavage cytology during endoscopic transpapillary catheterization into the gallbladder in the cytological diagnosis of gallbladder disease

Abstract: Many studies have reported methods of cell collection involving percutaneous transhepatic cholangiodrainage (PTCD) and fine-needle aspiration cytology for the diagnosis of gallbladder disease. However, few studies have described the use of a transpapillary approach, i.e., endoscopic transpapillary catheterization into the gallbladder (ETCG). In this study, we analyzed cells collected by ETCG to evaluate its usefulness in the cytological diagnosis of gallbladder disease. The subjects were 19 patients who had un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…TP smears were stained with Papanicolaou stain using routine laboratory protocol and were classified as inadequate, normal or benign, indeterminate, suspected malignancy, and malignant using the diagnostic criteria described in our previous report. 5…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TP smears were stained with Papanicolaou stain using routine laboratory protocol and were classified as inadequate, normal or benign, indeterminate, suspected malignancy, and malignant using the diagnostic criteria described in our previous report. 5…”
Section: Methodsmentioning
confidence: 99%
“…4 ERCP‐guided cytology, such as pancreatic juices, pancreatic brushing, and pancreatic washing, has common gained acceptance as a means of preoperative diagnosis of pancreatic disease, and this procedure is usually performed for cytological diagnosis in the pancreas and bile duct. 5, 6 The main disadvantage of using brushing cytology is human error, air‐drying artifacts, and cells being obscured by necrosis, inflammation, and red blood cells.…”
mentioning
confidence: 99%
“…In this meta‐analysis, lavage cytology improved the sensitivity to 45.8%. Lavage cytology has also been shown to be useful in diagnosing bile duct cancer and gallbladder diseases . Balloon catheters have been used for spot shooting of the desired area .…”
Section: Methodsmentioning
confidence: 99%
“…Lavage cytology has also been shown to be useful in diagnosing bile duct cancer and gallbladder diseases. 71,72 Balloon catheters have been used for spot shooting of the desired area. 73 In contrast, an evaluation of pancreatic juice cytology obtained by routine preoperative ERCP in 70 patients with IPMN found that the addition of pancreatic juice cytology altered treatment in two patients with branch-duct (BD)-IPMN from observation to surgical resection.…”
Section: Assessment Of Pancreatic Juice By a Transpapillary Approachmentioning
confidence: 99%
“…Gallbladder cancer has a tendency to seed the peritoneum, biopsy tracts, and surgical wounds (Fong et al, 1993;Hu et al, 2008;Merz et al, 1993), and unnecessary biopsies simply increase this risk. Sensitivity of bile cytology has been reported to be approximately 75% (Akosa et al, 1995;Arora et al, 2005;Mohandas et al, 1994;Naito et al, 2009). If the diagnosis is suspected, the surgeon and patient must be prepared for a definitive operation.…”
Section: Preoperative Pathologic Diagnosismentioning
confidence: 99%